Recommendations for the individualised management of atypical hemolytic uremic syndrome in adults - Ávila, Ana; Cao, Mercedes; Espinosa, Mario; Manrique, Joaquín; Morales, Enrique (Frontiers in Medicine, 2023)
Background Despite significant advances in therapeutic management of atypical hemolytic uremic syndrome (aHUS), guidelines are not timely updated and achieving a consensus on management recommendations remains a topic of ongoing discussion. Methods A Scientific Committee with five experts was set up. A literature review was conducted and publications addressing the classification of aHUS, patient profiles and therapeutic approach were selected. Recommendations were proposed at an initial meeting, evaluated through an online questionnaire and validated during a second meeting. Results Patients with confirmed or clear suspicion of aHUS should be treated with C5 inhibitors within 24 hours of the diagnosis or suspicion of aHUS. Treatment monitoring and the decision to interrupt treatment should be individualised according to the risk of relapse and each patient’s evolution. aHUS with a genetic variant or associated with pregnancy should be treated for at least 6-12 months; de novo aHUS associated with kidney transplant until renal function is recovered and genetic variants are ruled out; aHUS associated with malignant hypertension until genetic variants are ruled out; aHUS associated with non-kidney transplant, autoimmune diseases, infection- or drug-induced until the thrombotic microangiopathy is resolved. Patients with a high risk of relapse should be treated for longer than 6-12 months. Conclusions The START consensus provides physicians who are not familiar with the disease with recommendations for the management of aHUS in adults. The experts who participated advocate early treatment, maintenance for at least 6-12 months and treatment interruption guided by genetic background, trigger factors, risk of relapse and evolution.